Atomic structure of defects and dopants in 2D layered transition metal dichalcogenides. (5th July 2018) - Wang, Shanshan; Robertson, Alex; Warner, Jamie H.
Abstract : Transmission electron microscopy can directly image the detailed atomic structure of layered transition metal dichalcogenides, revealing defects and dopants. Abstract : Layered transition metal dichalcogenides (TMDs) offer monolayer 2D systems with diverse properties that extend beyond what graphene alone can achieve. The properties of TMDs are heavily influenced by the atomic structure and in particular imperfects in the crystallinity in the form of vacancy defects, grain boundaries, cracks, impurity dopants, ripples and edge terminations. This review will cover the current knowledge of the detailed structural forms of some of the most intensively studied 2D TMDs, such as MoS2, WSe2, MoTe2, WTe2, NbSe2, PtSe2, and also covers MXenes. The review will utilize results achieved using state-of-the-art aberration corrected transmission electron microscopy, including annular dark-field scanning transmission electron microscopy (ADF-STEM) and electron energy loss spectroscopy (EELS), showing how elemental discrimination can be achieved to understand structure at a deep level. The review will also cover the impact of single atom substitutional dopants, such as Cr, V and Mn, and electron energy loss spectroscopy used to understand the local bonding configuration. It is expected that this review will provide an atomic level understanding of 2D TMDs with a connection to imperfections that can arise from chemical vapour deposition synthesis, intentional doping, rips and tears, dislocations, strain, polycrystallinity and confinement to nanoribbons.